A negative feedback loop between fibroadipogenic progenitors and muscle fibres involving endothelin promotes human muscle fibrosis. Issue 3 (22nd March 2022) - Bensalah, Mona; Muraine, Laura; Boulinguiez, Alexis; Giordani, Lorenzo; Albert, Victorine; Ythier, Victor; Dhiab, Jamila; Oliver, Alison; Hanique, Valentine; Gidaro, Teresa; Perié, Sophie; Lacau St‐Guily, Jean; et al.
Abstract: Background: Fibrosis is defined as an excessive accumulation of extracellular matrix (ECM) components. Many organs are subjected to fibrosis including the lung, liver, heart, skin, kidney, and muscle. Muscle fibrosis occurs in response to trauma, aging, or dystrophies and impairs muscle function. Fibrosis represents a hurdle for the treatment of human muscular dystrophies. While data on the mechanisms of fibrosis have mostly been investigated in mice, dystrophic mouse models often do not recapitulate fibrosis as observed in human patients. Consequently, the cellular and molecular mechanisms that lead to fibrosis in human muscle still need to be identified. Methods: Combining mass cytometry, transcriptome profiling, in vitro co‐culture experiments, and in vivo transplantation in immunodeficient mice, we investigated the role and nature of nonmyogenic cells (fibroadipogenic progenitors, FAPs) from human fibrotic muscles of healthy individuals (FibM CT ) and individuals with oculopharyngeal muscular dystrophy (OPMD; FibM OP ), as compared with nonmyogenic cells from human nonfibrotic muscle (M CT ). Results: We found that the proliferation rate of FAPs from fibrotic muscle is 3–4 times higher than those of FAPs from nonfibrotic muscle (population doubling per day: M CT 0.2 ± 0.1, FibM CT 0.7 ± 0.1, and FibM OP 0.8 ± 0.3). When cocultured with muscle cells, FAPs from fibrotic muscle impair the fusion index unlike M CT FAPs (myoblasts alone 57.3 ± 11.1%, coculture with M CT 43.1 ± 8.9%, with FibM CT 31.7 ± 8.2%, and with FibM OP 36.06 ± 10.29%). We also observed an increased proliferation of FAPs from fibrotic muscles in these co‐cultures in differentiation conditions (FibM CT +17.4%, P <  0.01 and FibM OP +15.1%, P <  0.01). This effect is likely linked to the increased activation of the canonical TGFβ‐SMAD pathway in FAPs from fibrotic muscles evidenced by pSMAD3 immunostaining ( P  < 0.05). In addition to the profibrogenic TGFβ pathway, we identified endothelin as a new actor implicated in the altered cross‐talk between muscle cells and fibrotic FAPs, confirmed by an improvement of the fusion index in the presence of bosentan, an endothelin receptor antagonist (from 33.8 ± 10.9% to 52.9 ± 10.1%, P  < 0.05). Conclusions: Our data demonstrate the key role of FAPs and their cross‐talk with muscle cells through a paracrine signalling pathway in fibrosis of human skeletal muscle and identify endothelin as a new druggable target to counteract human muscle fibrosis.